Spectacles and Refractive Errors: Children’s Perspective - Amit Maitreya; Renu Dhasmana (Delhi Journal of Ophthalmology)
Purpose:- To study common perceptions in children about the use of spectacles as well as refractive error and problems faced by these children while using spectacles. Methods:- This was a hospital-based observational study conducted over a period of 2 months in children between 5 to 15 years of age using spectacles. A self-designed, standardized, prevalidated questionnaire was provided and answers were evaluated. Data thus obtained was subjected to standard statistical analysis. Results:- Among 55 children in the study, twenty-nine (52.7%) were male and twenty-six (47.3%) were female, with a male-female ratio of 1.1:1. Their average age was 11± 2.8 years. 41.8% children felt that wearing spectacles is a sign of intelligence. 85.5% were of the opinion that if they do not use spectacles, their refractive power will increase. 10.9% children said that the continuous use of spectacles will lead to an increase in their power. 52.7% considered nutritional deficiency as a common cause of refractive error while 67.3% children thought that yoga or diet or traditional medicines or a combination of these can reduce the refractive error. 45.5% felt that they faced problems due to the use of spectacles. 47.3% were teased for using spectacles and 43.6% children considered spectacles as a cosmetic blemish. 36.4% children accepted that they feel ashamed or embarrassed in using spectacles. Conclusion:- Knowledge in children regarding use of spectacles and refractive errors is not very encouraging. Children do face problems in using spectacles. There is potential for incorporation of correct information in the curriculum and teachers' training program.